Analysing the styles of thinking among primary school teachers - Kamarulzaman, Wirawani; Oo, Cheng Keat; Mohd Jodi, Khairul Hamimah; Che Aziz, Raziana; Mahmood, Rosinah (Global Academic Excellence (M) Sdn Bhd, 2021)
One of the focuses of Malaysian National Philosophy is the holistic development of individuals, which includes the ability to think in higher order. Teachers are the most important agents in the teaching process, so it's critical to pay attention to their capacity to teach students the skills. As a result, the purpose of this research is to examine teachers' thinking abilities and determine if there are any differences between genders. The Teaching Skills Inventory was completed by 266 primary school teachers in the Selangor area, and the results revealed that teachers use executive thinking skills. Despite the fact that both genders preferred executive thinking skills, a t-test indicates that male teachers scored significantly higher in all of Sternberg's suggested thinking styles. At the conclusion of the study, some recommendations for future research were included.